2015
DOI: 10.1007/s00125-015-3776-4
|View full text |Cite
|
Sign up to set email alerts
|

The insulin resistance phenotype (muscle or liver) interacts with the type of diet to determine changes in disposition index after 2 years of intervention: the CORDIOPREV-DIAB randomised clinical trial

Abstract: Although both diets improve insulin sensitivity, there are differences based on basal IR phenotypes. Moreover, according to insulinogenic and disposition index data, a low-fat diet might be more beneficial to patients with liver IR, whereas patients with muscle IR and muscle + liver IR might benefit more from a Mediterranean diet. Trial registration ClinicalTrials.gov NCT00924937 FUNDING: The study was supported by the Ministerio de Economia y Competitividad (AGL2012/39615) and by the Ministerio de Ciencia e I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
83
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 38 publications
1
83
1
Order By: Relevance
“…There is a strongly increasing interest in this type of biomarker in nutrition and health studies, demonstrating their use in uncovering early alterations in metabolism preceeding chronic diseases [9,[11][12][13][14]. Recently, it was shown that quantification of challenge response significantly contributes to demonstrating health effects of food and nutrition in dietary intervention studies [6,7,[14][15][16][17][18]. A standardized optimal nutritional challenge test was defined after performance of a systematic literature review [3].…”
Section: Introductionmentioning
confidence: 99%
“…There is a strongly increasing interest in this type of biomarker in nutrition and health studies, demonstrating their use in uncovering early alterations in metabolism preceeding chronic diseases [9,[11][12][13][14]. Recently, it was shown that quantification of challenge response significantly contributes to demonstrating health effects of food and nutrition in dietary intervention studies [6,7,[14][15][16][17][18]. A standardized optimal nutritional challenge test was defined after performance of a systematic literature review [3].…”
Section: Introductionmentioning
confidence: 99%
“…Although, due to the longitudinal character of CORDIOPREV, the clinical outcomes will not be unveiled until the end of the intervention periods, several papers have been already published from baseline data from the CORDIOPREV study which have yielded useful insights about genetics, human metabolism or inflammation. 3540 From the conceptual point of view, this study will fill the gap in long-term studies on secondary prevention using dietary approaches. Moreover, it will contribute to our understanding of the use of more personalized strategies.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, recently published papers from CordioPrev dealing with genetics or postprandial lipemia used ANOVA tests for quantitative variables and Chi-square for qualitative variables 3540 . As a general rule, all levels of significance for regular tests will be set at α=0.05, and Parametric tests will be used whenever possible.…”
Section: Methods and Designmentioning
confidence: 99%
“…As regards diabetic status at baseline, 540 of the subjects were T2DM patients and 462 were nondiabetics who had not been diagnosed with T2DM in the CORDIOPREV study . Of these, 107 patients developed T2DM according to the American Diabetes Association (ADA) diagnosis criteria after a median follow‐up of 59 months.…”
Section: Methodsmentioning
confidence: 99%